A clinical study of surgical management of paediatric humeral supracondylar fracture - Kumar, Ajay; Padmanabhan, Karthik (International Journal of Research in Orthopaedics, 2019)
Background: Injury to the supracondylar region of the humerus and complete displacement of the fragments occurs in many of the cases when children usually fall while playing. This is most common fracture seen in children, makes up to 60% of all elbow injuries. Early intervention results in excellent reduction and avoids complications. Concomitant vascular and nerve damages may occur. Open reduction and internal fixation is a helpful option for the treatment of supracondylar facture of humerus in children. Methods: Forty children who presented with displaced supracondylar fracture of the humerus were treated with open reduction and internal fixation with Kirschner (K) wires after thorough pre-operative investigation during the course of the study. Children below the age of 13 were selected irrespective of the sex. Results: Good results were obtained in 60% of the patients, fair in 30% and poor in 10%. The poor results were due to the open fracture and in two cases the patient presented very late to the hospital. Complications such as nerve injuries, vascular injuries, infections were noticed in the study. Four patients had cubitus varus and twelve patients had flexion loss on follow-up study. Conclusions: Open reduction and internal fixation with K wire is an easy, simple, inexpensive method, which has good outcome.